Adipose tissue adaptive response to trans‐10, cis‐12‐conjugated linoleic acid engages alternatively activated M2 macrophages. Issue 1 (11th September 2015) - Pini, Maria; Touch, Sothea; Poirier, Helene; Dalmas, Elise; Niot, Isabelle; Rouault, Christine; Druart, Celine; Delzenne, Nathalie; Clément, Karine; André, Sebastien; Guerre‐Millo, Michele
ABSTRACT: In mice, nutritional supplementation with the trans‐10, cis ‐12 isomer of linoleic acid (t10, c12‐CLA) promotes lipoatrophy, hyperinsulinemia, and macrophage infiltration in white adipose tissue (WAT). We explored the dynamics of these interrelated responses over 2 consecu‐five 7 d periods of t10, c12‐CLA administration and withdrawal. t10, c12‐CLA down‐regulated lipogenic and lipolytic gene expression and increased collagen deposition, but with no evidence of cross‐linking. An abundant CD45 + cell infiltrate, comprising prominently CD206 + CD11c ‐ macrophages, was found in WAT in association with an anti‐inflammatory gene signature. Infiltration of natural killer (NK) and dendritic cells contributed to WAT's innate immune response to t10, d12‐CLA. Less abundant adaptive immune cells colonized WAT, including B, NK T, γδ T, and αβ T cells. By contrast, T‐regulatory cell abundance was not affected. Interruption of treatment allowed recovery of WAT mass and normalization of insulinemia, coincident with regain of WAT homeostasis owing to a coordinated reversion of genic, structural, and immune deregulations. These data revealed a striking resilience of WAT after a short‐term metabolic injury induced by t10, d2‐CLA which relies on alternatively activated M2 macrophage engagement. In addition, the temporal links between variations in WAT alterations and insulinemia upon t10, c12‐CLA manipulation strengthen the view that WAT dysfunctional status is critically involved in altered glucose homeostasis.—Pini, M., Touch, S., Poirier, H., Dalmas, E., Niot, I., Rouault, C., Druart, C., Delzenne, N., Clément, K., André, S., Guerre‐Millo, M. Adipose tissue adaptive response to trans ‐10, cis ‐12‐conjugated linoleic acid engages alternatively activated M2 macrophages. FASEB J. 30, 241‐251 (2016). www.fasebj.org